Genetics of coronary artery disease: should they impact the choice of revascularization?. (November 2018) - Hui, Sonya K.; Lindale, Emma; Sun, Louise; Ruel, Marc
Abstract : Purpose of review: Patients with multivessel coronary artery disease (CAD) may undergo revascularization by either percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery (CABG). This review will discuss the use of polygenic risk scores for risk-stratification of patients with multivessel CAD in order to guide the choice of revascularization. Recent findings: A 57-single nucleotide polymorphism (SNP)-polygenic risk score can accurately risk-stratify patients with CAD and identify those who will receive greater benefit from statin therapy. The most recent genomic studies reveal 243 different SNPs are now significantly associated with CAD. Randomized clinical trials comparing PCI vs. CABG (FREEDOM, SYNTAX, NOBLE, EXCEL) have uncovered factors related to CAD severity (diabetes, SYNTAX score) are critical determinants of outcomes after revascularization. Summary: There is a need to discover predictors of outcomes after PCI vs. CABG to improve clinical decision-making in multivessel CAD. High polygenic risk score is associated with increased CAD severity and better outcomes with statin therapy. Randomized clinical trials indicate CAD severity is associated with better outcomes after CABG compared with PCI. Accordingly, polygenic risk score could also be associated with better outcomes after CABG vs. PCI and used to optimize revascularization for patients with multivessel CAD.